Aegean Wine Imports to the City of Rome (1st century BC – 3rd century AD) - Paulina Komar (Ksiegarnia Akademicka Publishing, 2019)
This paper investigates the imports of Aegean wines to the city of Rome between the Late Republican and the Middle Imperial period (1st century BC – 3rd century AD). Its main aim is to show the share of the Roman wine market that was supplied by the Aegean region, as well as investigating which areas of the Aegean were the main wine exporters.